Zika Virus Preparedness and Response Efforts Through the Collaboration Between a Health Care Delivery System and a Local Public Health Department. (7th March 2018) - Madad, Syra; Tate, Anna; Rand, Maytal; Quinn, Celia; Vora, Neil M.; Allen, Machelle; Cagliuso, Nicholas V.; Rakeman, Jennifer L.; Studer, Sean; Masci, Joseph; Varma, Jay K.; Wilson, Ross
ABSTRACT: The Zika virus was largely unknown to many health care systems before the outbreak of 2015. The unique public health threat posed by the Zika virus and the evolving understanding of its pathology required continuous communication between a health care delivery system and a local public health department. By leveraging an existing relationship, NYC Health+Hospitals worked closely with New York City Department of Health and Mental Hygiene to ensure that Zika-related processes and procedures within NYC Health+Hospitals facilities aligned with the most current Zika virus guidance. Support given by the public health department included prenatal clinical and laboratory support and the sharing of data on NYC Health+Hospitals Zika virus screening and testing rates, thus enabling this health care delivery system to make informed decisions and practices. The close coordination, collaboration, and communication between the health care delivery system and the local public health department examined in this article demonstrate the importance of working together to combat a complex public health emergency and how this relationship can serve as a guide for other jurisdictions to optimize collaboration between external partners during major outbreaks, emerging threats, and disasters that affect public health. ( Disaster Med Public Health Preparedness . 2018;12:689-691)